Strategi Guru Pendidikan Agama Islam Profesional Dalam Meningkatkan Kualitas Pembelajaran (Studi Kasus Di Smp Negeri 29 Surabaya Dan Smp Negeri 20 Malang) - Alfi Nurlalita Devi (Universitas Yudharta Pasuruan, 2021)
This study aims to describe about profiles, efforts and impacts of professional Islamic Education teacher in improving the quality of learning at SMP Negeri 29 Surabaya and SMP Negeri 20 Malang. This study uses a qualitative approach with case study type, where collecting data is conducted by interview, observation and documentation. The data obtained were then analyzed using the interactive analysis technique of Miles, Huberman and Saldana consisting of data condensation, data presentation and data verification. Checking the validity of the data is conducted by triangulation technique. The results of this study are 1) the profiles of professional Islamic Education teacher in improving the quality of learning is to have the criteria as a preacher of Islam, as the executor of the values of Islamic teachings and as an example of a good and true religious community. 2) the efforts of professional Islamic Education teacher in improving the quality of learning that are making preparations by compiling lesson plans, optimizing the implementation of learning, developing variations in learning methods, maximizing the use of online-based media as recommended by the government such as youtube, whatsapp group, microsoft teams 365, google classroom, and maximize the evaluation of cognitive, affective and psychomotor domains through online media. 3) the impacts of professional Islamic Education teachers in improving the quality of learning have shown a significant improvement in the quality of learning. This is proven by the achievement results of students get very good achievement scores.